Positive electrode active material, its manufacturing method and lithium secondary battery including the same
A phase gradient cobalt coating on high-nickel lithium composite transition metal oxides in lithium secondary batteries addresses resistance and gas issues, enhancing conductivity and storage characteristics.
Patent Information
- Application Number
- JP2024543536
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-04-01
- Filing Date
- 2023-04-03
- Publication Date
- 2025-01-30
- Estimated Expiration
- 2043-04-03
AI Technical Summary
High-nickel positive active materials in lithium secondary batteries face issues such as increased resistance and gas generation due to the formation of a cobalt coating layer that facilitates lithium loss and side reactions with the electrolytic solution.
A phase gradient coating containing cobalt is applied to high-nickel single particle lithium composite transition metal oxides, forming a gradient from a spinel structure to a layer structure, which enhances conductivity and prevents lithium loss.
The phase gradient coating reduces initial resistance and improves high-temperature storage characteristics by maintaining lithium within the positive electrode and minimizing gas generation.
Smart Images

Figure 2025503124000001_ABST
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0041203 filed on April 1, 2022, the entire contents of which are incorporated herein by reference.
[0002] The present invention relates to a positive electrode active material including a high-nickel (High-Ni)-based single-particle lithium transition metal composite oxide, which improves the initial resistance characteristics of a lithium secondary battery by introducing a coating part including cobalt having a phase gradient, prevents side reactions with an electrolyte, and suppresses the amount of gas generation, and relates to a positive electrode active material, a manufacturing method thereof, and a lithium secondary battery including the same. [Background technology]
[0003] Recently, with the development of technologies such as electric vehicles, the need for high-capacity secondary batteries is increasing, and as a result, research on high-nickel (High-Ni) positive electrode active materials with excellent capacity characteristics is being actively conducted.
[0004] However, when the nickel content of the positive electrode active material is high, problems such as capacity reduction and resistance occur as the battery cycle progresses. To solve these problems, research is being conducted on various coating materials.
[0005] When cobalt, a typical coating material, is applied to the surface of a high-nickel positive active material, a coating layer containing cobalt is formed on the surface. In this case, in the existing coating method, the coating layer containing cobalt is formed in a layered structure, which makes it easy for lithium to be separated from the positive active material and increases the viscosity of the slurry used to form the positive electrode, resulting in problems such as an increase in the initial resistance of the battery and an increase in the amount of gas generated by the battery. Summary of the Invention [Problem to be solved by the invention]
[0006] The present invention is an invention for solving the above problems, and an object of the present invention is to provide a positive electrode active material containing a high-nickel (High-Ni)-based single-particle lithium transition metal composite oxide, which improves the initial resistance characteristics of a lithium secondary battery, prevents side reactions with an electrolyte, and suppresses the amount of gas generation.
[0007] In addition, the present invention provides a method for manufacturing the positive electrode active material, the method having a phase gradient and capable of introducing a coating portion containing cobalt.
[0008] Another object of the present invention is to provide a lithium secondary battery which contains the above positive electrode active material and has low initial resistance and improved storage characteristics. [Means for solving the problem]
[0009] In order to solve the above problems, the present invention provides a positive electrode active material, a method for producing a positive electrode active material, a positive electrode, and a lithium secondary battery.
[0010] (1) The present invention provides a positive electrode active material comprising: a single-particle lithium transition metal oxide; and a coating portion containing cobalt formed on the single-particle lithium transition metal oxide, wherein the coating portion containing cobalt has a phase gradient from a spinel structure to a layered structure from a surface to a center of the positive electrode active material.
[0011] (2) The present invention provides a positive electrode active material according to the above (1), wherein the lithium transition metal composite oxide in the form of a single particle contains 60 mol % or more of nickel relative to the total number of moles of metals other than lithium.
[0012] (3) The present invention provides a positive electrode active material according to the above (1) or (2), wherein the lithium transition metal composite oxide in the form of a single particle has a composition represented by the following Chemical Formula 1: [Chemical formula 1] Li x [Ni a Co b Mn c M1 d ]O 2-y A y In the above Chemical Formula 1, M1 is one or more selected from Y, Zr, Al, B, Ti, W, Nb, Sr, Mo, and Mg; A is one or more selected from F, Cl, Br, I and S; 0.9≦x≦1.2, 0.6≦a<1, 0≦b≦0.4, 0≦c≦0.4, 0≦d≦0.2, a+b+c+d=1, 0≦y≦0.2.
[0013] (4) The present invention provides a positive electrode active material according to any one of the above (1) to (3), wherein the coating portion containing cobalt is present locally on a surface of the positive electrode active material.
[0014] (5) In any one of the above (1) to (4), the coating portion containing cobalt has a spinel structure of Co3O4, Li 0.5 The present invention provides a positive electrode active material having a phase gradient of a spinel structure of CoO2 and a layered structure of LiCoO2.
[0015] (6) The present invention provides the positive electrode active material according to any one of (1) to (5) above, wherein the cobalt-containing coating portion further contains aluminum.
[0016] (7) The present invention also relates to a lithium composite transition metal oxide in the form of a single particle and an average particle size (D 50 and heat-treating the mixture.
[0017] (8) The present invention provides the method for producing a positive electrode active material according to the above (7), wherein the mixture contains the cobalt oxide in an amount such that a ratio (B / A) of a number of moles (B) of cobalt contained in the cobalt oxide to a total number of moles (A) of metals other than lithium contained in the lithium composite transition metal oxide is 0.1 to 5.
[0018] (9) The present invention provides the method for producing a positive electrode active material according to (7) or (8), wherein the mixture further contains an aluminum source material.
[0019] (10) The present invention provides the method for producing a positive electrode active material according to (9), wherein the mixture contains the aluminum raw material in an amount of 0.01 part by weight to 0.1 part by weight based on 100 parts by weight of the lithium composite transition metal oxide.
[0020] (11) The present invention provides the method for producing a positive electrode active material according to any one of the above (7) to (10), wherein the heat treatment is carried out in an oxygen atmosphere.
[0021] (12) The present invention provides the method for producing a positive electrode active material according to any one of the above (7) to (11), wherein the heat treatment is carried out at a temperature of 600°C to 800°C.
[0022] (13) The present invention provides the method for producing a positive electrode active material according to any one of the above (7) to (12), wherein the heat treatment is carried out for 1 hour to 8 hours.
[0023] (14) The present invention also provides a positive electrode comprising the positive electrode active material according to any one of (1) to (6) above.
[0024] (15) The present invention also provides a lithium secondary battery comprising the positive electrode according to (14) above, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte. Effect of the Invention
[0025] The positive electrode active material of the present invention includes a high-nickel (High-Ni)-based single particle type lithium transition metal composite oxide, and has a phase gradient from a spinel structure to a layer structure from the surface to the center of the positive electrode active material. A coating portion containing cobalt is introduced, thereby improving the initial resistance characteristics of a lithium secondary battery and minimizing the amount of gas generation.
[0026] In addition, according to the method for manufacturing a positive electrode active material of the present invention, a coating portion having a phase gradient and containing cobalt can be effectively introduced. [Brief description of the drawings]
[0027] [Figure 1] 1 shows EPMA (Electron Probe X-ray Micro Analyzer) data for the positive electrode active material of Example 1. [Diagram 2] 1 is a TEM (Transmission Electron Microscope) image of the positive electrode active material of Example 1. [Diagram 3] 1 is a TEM image of the positive electrode active material of Comparative Example 1. [Figure 4] 1 is a scanning electron microscope (SEM) image of a single particle type lithium transition metal composite oxide used in Examples and Comparative Examples. [Diagram 5] 1 is a SEM image of the positive electrode active material of Example 1. [Figure 6] 1 is a SEM image of the positive electrode active material of Example 2. [Figure 7] 1 is a SEM image of the positive electrode active material of Comparative Example 1. [Figure 8] 1 is an SEM image of the positive electrode active material of Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0028] The present invention will now be described in further detail in order to facilitate understanding of the present invention.
[0029] The terms and words used in this specification and the claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a manner that is consistent with the technical idea of the present invention, based on the principle that the inventors can appropriately define the concepts of terms in order to best describe their invention.
[0030] In this specification, the terms "comprise", "comprise", "have" and the like are intended to specify the presence of embodied features, numbers, steps, components, or combinations thereof, but are not intended to preclude the presence or additional possibility of one or more different features, numbers, steps, components, or combinations thereof.
[0031] As used herein, the term "on" is meant to include not only cases where one structure is formed immediately on top of another structure, but also cases where a third structure is interposed between the structures.
[0032] In this specification, the term "single-particle positive electrode active material" refers to a positive electrode active material consisting of 10 or less primary particles, as opposed to a spherical secondary particle positive electrode active material produced by a conventional method, which is formed by agglomeration of tens to hundreds of primary particles. Specifically, in the present invention, the single-particle positive electrode active material may be a single particle consisting of one primary particle, or may be a secondary particle formed by agglomeration of several primary particles.
[0033] The term "primary particle" refers to the smallest particle unit that can be recognized when observing a positive electrode active material through a scanning electron microscope, and the term "secondary particle" refers to a secondary structure formed by aggregation of a plurality of primary particles.
[0034] As used herein, the term “average particle size (D 50The "average particle size" refers to the particle size at the 50% point of the cumulative volume distribution by particle size. The average particle size is determined by dispersing the powder to be measured in a dispersion medium, introducing it into a commercially available laser diffraction particle size measuring device (e.g., S3500 manufactured by Microtrac), measuring the difference in the diffraction pattern due to the particle size when the particles pass through a laser beam, calculating the particle size distribution, and calculating the particle diameter at the 50% point of the cumulative volume distribution by particle size in the measuring device. 50 can be measured.
[0035] positive electrode active material The present invention provides a positive electrode active material comprising: a single-particle lithium composite transition metal oxide; and a coating portion containing cobalt formed on the single-particle lithium composite transition metal oxide, wherein the coating portion containing cobalt has a phase gradient from a spinel structure to a layered structure from a surface to a center of the positive electrode active material.
[0036] The present inventors have found that when a coating portion having a phase gradient is formed on the single-particle lithium composite transition metal oxide, specifically, when a coating portion containing cobalt having a phase gradient from a spinel structure to a layered structure is formed from the surface to the center of the positive electrode active material, not only does the electrical conductivity increase, but the lithium present inside the positive electrode active material is prevented from being released, improving the initial resistance characteristics and storage characteristics (particularly, high-temperature storage characteristics) of the lithium secondary battery, and have completed the present invention.
[0037] As used herein, phase gradient refers to a change in the crystal lattice structure, such as a layered structure, a spinel structure, or the like. Specifically, phase gradient can refer to a gradual change in the crystal lattice structure as the composition of the coating changes. For example, when the composition of the coating is Li x When it is CoO2, it may mean that the crystal lattice structure gradually changes as the x value gradually changes from 1 to 0.5.
[0038] According to the present invention, the lithium composite transition metal oxide in the form of a single particle may contain nickel in an amount of 60 mol% or more, specifically 80 mol% or more, more specifically 85 mol% or more, based on the total moles of metals other than lithium. That is, the lithium composite transition metal oxide in the form of a single particle may be a high nickel (High Ni)-based lithium composite transition metal oxide. In this case, the energy density of a lithium secondary battery may be improved.
[0039] According to the present invention, the lithium transition metal composite oxide in the form of a single particle may have a composition represented by the following Chemical Formula 1.
[0040] [Chemical formula 1] Li x [Ni a Co b Mn c M1 d ]O 2-y A y
[0041] In the above Chemical Formula 1, M1 is one or more selected from Y, Zr, Al, B, Ti, W, Nb, Sr, Mo, and Mg; A is one or more selected from F, Cl, Br, I and S; 0.9≦x≦1.2, 0.6≦a<1, 0≦b≦0.4, 0≦c≦0.4, 0≦d≦0.2, a+b+c+d=1, 0≦y≦0.2.
[0042] Specifically, M1 can be one or more selected from Y, Zr, and Al.
[0043] The a means the atomic fraction of nickel among the metal elements in the lithium composite transition metal oxide, and may be 0.6≦a<1, 0.8≦a≦0.98, or 0.85≦a≦0.95.
[0044] The b represents the atomic fraction of cobalt among the metal elements in the lithium composite transition metal oxide, and may be 0≦b≦0.4, 0.01≦b≦0.2, or 0.01≦b≦0.15.
[0045] The c represents the atomic fraction of manganese among the metal elements in the lithium composite transition metal oxide, and may be 0≦b≦0.4, 0.01≦b≦0.2, or 0.01≦b≦0.15.
[0046] The d means the atomic fraction of the M1 element among the metal elements in the lithium composite transition metal oxide, and may be 0≦d≦0.2, 0≦d≦0.1, or 0≦d≦0.05.
[0047] The lithium transition metal composite oxide in the form of a single particle has an average particle size (D 50 ) can be from 1 μm to 10 μm, specifically from 1 μm to 7 μm, and more specifically from 1 μm to 5 μm.
[0048] According to the present invention, the coating portion including cobalt may be present locally on the surface of the positive electrode active material in terms of improving lithium ion conductivity. That is, the coating portion may not cover the entire surface of the lithium composite transition metal oxide in the form of a single particle. Here, the coating portion may have a dot shape. Meanwhile, the coating portion may not be present at a grain boundary.
[0049] According to the present invention, the coating portion including cobalt has a phase gradient from a spinel structure to a layered structure from the surface to the center of the positive active material, which not only increases the conductivity but also prevents lithium present inside the positive active material from being released, thereby improving the initial resistance characteristics and high-temperature storage characteristics of the lithium secondary battery.
[0050] According to the present invention, the coating portion containing cobalt has a spinel structure of Co3O4, Li0.5 It is possible to have a phase gradient of the spinel structure of CoO2 and the layered structure of LiCoO2. In this case, the spinel structure of Co3O4, Li 0.5 The spinel structure of CoO2 not only has excellent electrical conductivity, but also 0.5 Since the spinel structure of CoO2 has high lithium ion conductivity, the initial resistance of a battery using the positive electrode active material can be lowered. Also, since the spinel structure of Co3O4, which is a structure in which lithium cannot move, is present at the outermost edge, lithium can be more effectively prevented from being separated from the positive electrode active material, and the storage characteristics of a battery using the positive electrode active material can be further improved.
[0051] According to the present invention, the coating portion containing cobalt may further contain aluminum. In this case, the lithium ion conductivity of the coating portion may be improved, and when the positive electrode active material is applied to a battery, the initial resistance characteristic and storage characteristic of the battery may be more excellent. Here, the coating portion containing cobalt and aluminum may be locally present on the surface of the positive electrode active material and have a dot shape.
[0052] The aluminum may be included in the lithium composite transition metal oxide in an amount of 100 ppm to 1,000 ppm, 200 ppm to 700 ppm, or 400 ppm to 600 ppm. In this case, the dot-shaped coating portion is distributed in an appropriate size and amount, so that when the positive electrode active material is applied to a battery, the electrochemical characteristics of the battery can be improved.
[0053] Method for producing positive electrode active material The present invention relates to a lithium composite transition metal oxide in the form of a single particle and an average particle size (D 50 and heat-treating the mixture.
[0054] The above-mentioned positive electrode active material according to the present invention is manufactured by the method for manufacturing a positive electrode active material according to the present invention. That is, a lithium composite transition metal oxide in the form of a single particle and an average particle diameter (D 50 When a mixture containing a cobalt oxide having a particle size of 50 nm to 1000 nm is prepared and the mixture is heat-treated, a coating portion containing cobalt is formed on the lithium composite transition metal oxide in the form of a single particle, and the coating portion containing cobalt has a phase gradient (specifically, a phase gradient from a spinel structure to a layer structure from the surface to the center of the positive electrode active material).
[0055] As in the present invention, the average particle size (D 50 When a cobalt oxide having an average particle diameter (D) of 50 nm to 1000 nm is used as a raw material, a coating portion containing cobalt having a phase gradient from a spinel structure to a layer structure from the surface to the center of the positive electrode active material can be formed. 50 When using cobalt oxide with an average particle size (D) of less than 50 nm as the raw material for the coating, the diffusion is too fast and the coating is not formed, and the cobalt diffuses into the lithium composite transition metal oxide. 50 When cobalt oxide having a diameter exceeding 1000 nm is used as the raw material for the coating portion, there is a problem that the cobalt oxide remains in a solidified state.
[0056] According to the present invention, the cobalt oxide has an average particle size (D 50 ) may be 50 nm to 1000 nm, specifically 50 nm to 300 nm, and more specifically 50 nm to 200 nm. In this case, the coating portion may not be formed on the grain boundary, but may be formed locally on the surface of the positive electrode active material.
[0057] The cobalt oxide may be at least one selected from Co3O4, Co2O3, and CoO, and may be specifically Co3O4.
[0058] According to the present invention, the mixture may contain the cobalt oxide in an amount such that the ratio (B / A) of the number of moles of cobalt (B) contained in the cobalt oxide to the total number of moles (A) of metals other than lithium contained in the lithium composite transition metal oxide is 0.1 to 5, specifically 0.5 to 4, and more specifically 1 to 2.5. In this case, the formed coating portion can be controlled to have a desired phase, morphology, etc., and as a result, the resistance characteristics and high-temperature storage characteristics of a battery including the manufactured positive electrode active material can be further improved.
[0059] According to the present invention, the mixture may further include an aluminum source material. In this case, aluminum may more precisely control the shape of the coating portion, and may eliminate cation mixing, thereby improving lithium ion conductivity. As a result, the structural stability and lithium ion conductivity of the prepared positive electrode active material are improved, and when the positive electrode active material is applied to a battery, the initial resistance characteristics and storage characteristics of the battery may be further improved. For reference, when the mixture further includes an aluminum source material, more dot-shaped coating portions may be formed.
[0060] According to the present invention, the mixture may contain the aluminum source material in an amount of 0.01 to 0.1 parts by weight, specifically 0.02 to 0.07 parts by weight, and more specifically 0.04 to 0.06 parts by weight, based on 100 parts by weight of the lithium composite transition metal oxide. In this case, the dot-shaped coating portion may be distributed in an appropriate size and amount, and the structural stability of the prepared positive electrode active material may be improved, and when the same is applied to a battery, the resistance characteristics and high-temperature storage stability of the battery may be further improved.
[0061] The aluminum source material may be one or more selected from Al(OH)2, Al2O3, AlCl3, Al(NO)3, and AlSO4, specifically, one or more selected from Al(OH)2, Al2O3, and Al(NO)3, and more specifically, Al(OH)2.
[0062] According to the present invention, the heat treatment can be carried out in an oxygen atmosphere to prevent the lithium transition metal oxide from deteriorating into a rock salt structure.
[0063] According to the present invention, the heat treatment can be carried out at a temperature of 600°C to 800°C, specifically 650°C to 750°C, and more specifically 680°C to 730°C in order to form a coating portion having a desired phase.
[0064] According to the present invention, the heat treatment can be performed for 1 hour to 10 hours, specifically 2 hours to 8 hours, and more specifically 3 hours to 6 hours in order to control interdiffusion between the lithium transition metal oxide and the coating portion.
[0065] positive electrode The present invention provides a positive electrode comprising the positive electrode active material.
[0066] According to an embodiment of the present invention, the positive electrode may include a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector, and the positive electrode active material layer may include the positive electrode active material.
[0067] According to an embodiment of the present invention, the positive electrode current collector may include a metal having high conductivity, and may be easily attached to the positive electrode active material layer, and may be non-reactive in the voltage range of the battery. The positive electrode current collector may be, for example, stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. The positive electrode current collector may have a thickness of typically 3 μm to 500 μm, and may have fine irregularities on the surface of the current collector to enhance the adhesive strength of the positive electrode active material. For example, the positive electrode current collector may be used in various forms, such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0068] According to an embodiment of the present invention, the positive electrode active material layer may selectively include a conductive material and a binder, if necessary, together with the positive electrode active material. Here, the positive electrode active material may be included in an amount of 80 wt% to 99 wt%, more specifically, 85 wt% to 98.5 wt%, based on the total weight of the positive electrode active material layer, and within this range, excellent capacity characteristics may be exhibited.
[0069] According to an embodiment of the present invention, the conductive material is used to give conductivity to the electrode, and can be used without any particular limitation as long as it does not cause a chemical change in the battery constructed and has electronic conductivity. Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive tubes such as carbon nanotubes; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives, and among these, one type alone or a mixture of two or more types can be used. The conductive material can be included in an amount of 0.1% by weight to 15% by weight based on the total weight of the positive electrode active material layer.
[0070] According to an embodiment of the present invention, the binder serves to improve adhesion between the positive electrode active material particles and adhesion between the positive electrode active material and the current collector.Specific examples of the binder include polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, polymethyl methacrylate, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene butadiene rubber (SBR), fluorine rubber, polyacrylic acid, polymers in which hydrogen is substituted with Li, Na, or Ca, or various copolymers thereof, and the like, and one or more of these may be used alone or in combination. The binder may be included in an amount of 0.1% by weight to 15% by weight based on the total weight of the positive electrode active material layer.
[0071] According to an embodiment of the present invention, the positive electrode may be manufactured by a conventional method for manufacturing a positive electrode, except for using the positive electrode active material. Specifically, the positive electrode may be manufactured by applying a composition for forming a positive electrode active material layer, which is prepared by dissolving or dispersing the positive electrode active material and, if necessary, a binder, a conductive material, and a dispersant in a solvent, onto a positive electrode current collector, followed by drying and rolling, or by casting the composition for forming a positive electrode active material layer onto another support, followed by peeling the composition from the support, and laminating the resulting film onto a positive electrode current collector.
[0072] According to an embodiment of the present invention, the solvent may be a solvent commonly used in the art, and may include dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), dimethylformamide (DMF), acetone, water, etc., and one or more of these may be used alone or in combination. The amount of the solvent used is sufficient to dissolve or disperse the positive electrode active material, conductive material, binder, and dispersant in consideration of the coating thickness of the slurry and the manufacturing yield, and to have a viscosity that can show excellent thickness uniformity when applied to manufacture a positive electrode.
[0073] Lithium secondary battery The present invention provides a lithium secondary battery including the positive electrode.
[0074] According to an embodiment of the present invention, the lithium secondary battery may include the positive electrode, the negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte. The lithium secondary battery may further include a battery container that houses an electrode assembly of the positive electrode, the negative electrode, and the separator, and a sealing member that seals the battery container.
[0075] According to an embodiment of the present invention, the negative electrode may include a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector.
[0076] According to an embodiment of the present invention, the negative electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has high conductivity, and may be, for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy. The negative electrode current collector may have a thickness of typically 3 μm to 500 μm, and may have fine irregularities formed on the surface of the current collector, as with the positive electrode current collector, to strengthen the binding force of the negative electrode active material. For example, the negative electrode current collector may be used in various forms, such as a film, sheet, foil, net, porous body, foam, or nonwoven fabric.
[0077] According to an embodiment of the present invention, the negative electrode active material layer may optionally include a binder and a conductive material in addition to the negative electrode active material.
[0078] According to an embodiment of the present invention, the negative electrode active material may be a compound capable of reversible intercalation and deintercalation of lithium. Specific examples of the negative electrode active material include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys; SiO β(0<β<2), metal oxides capable of doping and dedoping lithium, such as SnO2, vanadium oxide, and lithium vanadium oxide; or composites containing the metallic compounds and carbonaceous materials, such as Si-C composites and Sn-C composites, and any one or a mixture of two or more of these may be used. In addition, a thin film of metallic lithium may be used as the negative electrode active material. In addition, both low-crystalline carbon and high-crystalline carbon may be used as the carbon material. Representative examples of low crystalline carbon include soft carbon and hard carbon, and representative examples of high crystalline carbon include amorphous, plate-like, flaky, spherical or fibrous natural graphite or artificial graphite, kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, meso-carbon microbeads, mesophase pitches, and high-temperature fired carbon such as petroleum or coal tar pitch derived cokes. The negative electrode active material may be included in an amount of 80 wt% to 99 wt% based on the total weight of the negative electrode active material layer.
[0079] According to an embodiment of the present invention, the binder of the negative electrode active material layer is a component that helps to bind between the conductive material, the active material, and the current collector, and is usually added in an amount of 0.1% by weight to 10% by weight based on the total weight of the negative electrode active material layer. Examples of such binders include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene-butadiene rubber, nitrile-butadiene rubber, fluororubber, and various copolymers thereof.
[0080] According to an embodiment of the present invention, the conductive material of the negative electrode active material layer is a component for further improving the conductivity of the negative electrode active material, and may be added in an amount of 10% by weight or less, preferably 5% by weight or less, based on the total weight of the negative electrode active material layer. Such a conductive material is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and examples of the conductive material include graphite such as natural graphite and artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; carbon fluoride; metal powders such as aluminum and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives.
[0081] According to an embodiment of the present invention, the negative electrode may be manufactured by coating a composition for forming a negative electrode active material layer, which is prepared by dissolving or dispersing a negative electrode active material, and optionally a binder and a conductive material, in a solvent, on a negative electrode current collector and drying the composition. Alternatively, the negative electrode active material layer may be manufactured by casting the composition for forming a negative electrode active material layer on a separate support, peeling it off from the support, and laminating the resulting film on the negative electrode current collector.
[0082] According to an embodiment of the present invention, the separator separates the negative electrode and the positive electrode and provides a path for lithium ions to move. Any separator that is generally used in lithium secondary batteries may be used without any particular limitation. In particular, a separator that has low resistance to ion movement of the electrolyte and has excellent electrolyte humidification ability is preferred. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof may be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of high-melting glass fiber, polyethylene terephthalate fiber, etc. may be used. In addition, a coated separator containing a ceramic component or a polymeric material may be used to ensure heat resistance or mechanical strength, and may be selectively used as a single layer or a multilayer structure.
[0083] According to an embodiment of the present invention, the electrolyte may be, but is not limited to, an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte, a molten inorganic electrolyte, etc. that can be used in manufacturing a lithium secondary battery. As a specific example, the electrolyte may include an organic solvent and a lithium salt.
[0084] According to an embodiment of the present invention, the organic solvent may be any solvent that can act as a medium through which ions involved in the electrochemical reaction of the battery can move. Specifically, the organic solvent may be an ester solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, or ε-caprolactone; an ether solvent such as dibutyl ether or tetrahydrofuran; a ketone solvent such as cyclohexanone; an aromatic hydrocarbon solvent such as benzene or fluorobenzene; dimethylcarbonate (DMC), diethylcarbonate (DEC), methylethylcarbonate (MEC), ethylmethylcarbonate (EMC), ethylene carbonate (EC), or propylene carbonate (propylene carbonate). Examples of the solvents that can be used include carbonate-based solvents such as polycarbonate (PC) and polycarbonate-based solvents such as ethyl alcohol and isopropyl alcohol; nitriles such as R-CN (R is a straight-chain, branched or cyclic hydrocarbon group having 2 to 20 carbon atoms, which may contain a double bond aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; and sulfolanes. Among these, carbonate-based solvents are preferred, and a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) having high ionic conductivity and high dielectric constant that can enhance the charge / discharge performance of a battery and a low-viscosity straight-chain carbonate compound (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) is more preferred.
[0085] According to one embodiment of the present invention, the lithium salt can be used without any particular limitation as long as it is a compound that can provide lithium ions used in a lithium secondary battery. Specifically, the anion of the lithium salt can be F - , Cl - , Br - , I - , NO3 - , N(CN)2 - , BF4 - , CF3CF2SO3 - , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - and (CF3CF2SO2)2N - The lithium salt may be at least one selected from the group consisting of LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2. The lithium salt is preferably used in a concentration range of 0.1M to 2.0M. When the lithium salt concentration is within the above range, the electrolyte has appropriate conductivity and viscosity, so that it can exhibit excellent electrolyte performance and lithium ions can move effectively.
[0086] According to an embodiment of the present invention, the electrolyte may further contain one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethyl alcohol amine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethyl alcohol, or aluminum trichloride, for the purpose of improving the life characteristics of the battery, suppressing the decrease in the capacity of the battery, improving the discharge capacity of the battery, etc. Here, the additives may be contained in an amount of 0.1% by weight to 5% by weight based on the total weight of the electrolyte.
[0087] The lithium secondary battery including the positive electrode active material according to the present invention stably exhibits excellent capacity characteristics, output characteristics and life characteristics, and is therefore useful in portable devices such as mobile phones, notebook computers and digital cameras, and in the field of electric vehicles such as hybrid electric vehicles (HEVs) and electric vehicles (EVs).
[0088] The external shape of the lithium secondary battery of the present invention is not particularly limited, and may be a cylindrical shape using a can, a square shape, a pouch shape, a coin shape, or the like.
[0089] The lithium secondary battery according to the present invention can be used as a battery cell used as a power source for a small device, and can also be preferably used as a unit battery in a medium- to large-sized battery module including a large number of battery cells.
[0090] According to an embodiment of the present invention, there is provided a battery module including the lithium secondary battery as a unit cell, and a battery pack including the same.
[0091] According to an embodiment of the present invention, the battery module or the battery pack may be used as a power source for one or more medium- to large-sized devices, such as a power tool; an electric vehicle (EV), a hybrid electric vehicle, and an electric vehicle (PHEV), including a plug-in hybrid electric vehicle; or a power storage system.
[0092] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will now be described in detail with reference to exemplary embodiments thereof, so that those skilled in the art can easily practice the present invention. However, the present invention may be embodied in many different forms and should not be construed as limited to the embodiments set forth herein. EXAMPLES
[0093] Examples and Comparative Examples Example 1 Single particle form of lithium composite transition metal oxide (composition: LiNi 0.86 Co 0.05 Mn 0.09 O2; average particle size (D 50 ): 4 μm) (LG Chemical Co., Ltd.) and average particle size (D 50 A mixture was prepared by uniformly mixing cobalt oxide (Co3O4) having a particle size of 200 nm with the lithium composite transition metal oxide in an amount such that the ratio of the number of moles of cobalt contained in the cobalt oxide to the total number of moles of metals other than lithium contained in the lithium composite transition metal oxide was 2. The mixture was heat-treated in an oxygen atmosphere at a temperature of 680° C. for 5 hours to prepare a positive electrode active material in which a coating portion containing cobalt was formed on the single-particle lithium composite transition metal oxide.
[0094] Example 2 Single particle form of lithium composite transition metal oxide (composition: LiNi 0.86 Co 0.05 Mn 0.09 O2; average particle size (D 50 ): 4 μm) (LG Chemical Co., Ltd.) and average particle size (D 50A mixture was prepared by uniformly mixing cobalt oxide (Co3O4) having a particle size of 200 nm and aluminum hydroxide (Al(OH)2) (KC Corporation) (the cobalt oxide was used in an amount such that the ratio of the number of moles of cobalt contained in the cobalt oxide to the total number of moles of metals other than lithium contained in the lithium composite transition metal oxide was 2, and the aluminum hydroxide was mixed in an amount of 0.05 parts by weight per 100 parts by weight of the lithium composite transition metal oxide). The mixture was heat-treated in an oxygen atmosphere at a temperature of 700° C. for 5 hours to prepare a positive electrode active material in which a coating portion containing cobalt and aluminum was formed on the single-particle lithium composite transition metal oxide.
[0095] Comparative Example 1 Single particle form of lithium composite transition metal oxide (composition: LiNi 0.86 Co 0.05 Mn 0.09 O2; average particle size (D 50 A mixture was prepared by uniformly mixing cobalt hydroxide (Co(OH)2) (manufactured by Huayou) in amounts such that the ratio of the number of moles of cobalt contained in the cobalt hydroxide to the total number of moles of metals other than lithium contained in the lithium composite transition metal oxide was 2. The mixture was heat-treated in an oxygen atmosphere at a temperature of 680° C. for 5 hours to prepare a positive electrode active material in which a coating layer containing cobalt was formed on the single-particle lithium composite transition metal oxide.
[0096] Comparative Example 2 Single particle form of lithium composite transition metal oxide (composition: LiNi 0.86 Co 0.05 Mn 0.09 O2; average particle size (D 50A mixture was prepared by uniformly mixing aluminium hydroxide (Al(OH)2) (manufactured by KC) and aluminium hydroxide (Co(OH)2) (manufactured by LG Chem), cobalt hydroxide (Co(OH)2) (manufactured by Huayou), and aluminum hydroxide (Al(OH)2) (manufactured by KC) (the cobalt hydroxide was used in an amount such that the ratio of the number of moles of cobalt contained in the cobalt hydroxide to the total number of moles of metals other than lithium contained in the lithium composite transition metal oxide was 2, and the aluminum hydroxide was mixed in an amount of 0.05 parts by weight per 100 parts by weight of the lithium composite transition metal oxide). The mixture was heat-treated in an oxygen atmosphere at a temperature of 700° C. for 5 hours to prepare a positive electrode active material in which a coating layer containing cobalt and aluminum was formed on the single particle lithium composite transition metal oxide.
[0097] Comparative Example 3 Average particle size (D 50 Instead of cobalt oxide (Co3O4) with an average particle size (D 50 A positive electrode active material was prepared in the same manner as in Example 2, except that cobalt oxide (Co3O4) having a particle size of 30 nm was used.
[0098] Comparative Example 4 Average particle size (D 50 Instead of cobalt oxide (Co3O4) with an average particle size (D 50 A positive electrode active material was prepared in the same manner as in Example 2, except that cobalt oxide (Co3O4) having a particle size of 1.5 μm was used.
[0099] Experimental Example Experimental example 1: Positive electrode active material analysis In order to confirm how the coating portion containing cobalt was formed on the surface of the positive electrode active material prepared in Example 1, an EPMA (Electron Probe X-ray Micro Analyzer) was used to analyze the surface, and the EPMA data is shown in FIG. 1.
[0100] In addition, the coating portions or coating layers of the positive electrode active materials prepared in Example 1 and Comparative Example 1 were observed using a TEM (Transmission Electron Microscope). The TEM image of Example 1 is shown in FIG. 2, and the TEM image of Comparative Example 1 is shown in FIG.
[0101] Referring to FIG. 1, in the case of Example 1 according to the present invention, it can be seen that a coating portion containing cobalt is locally formed on the surface of the positive electrode active material.
[0102] 2 and 3, in the case of Example 1, the positive electrode active material has a spinel structure of Co3O4 from the surface to the center, a Li 0.5 It can be seen that a coating portion having a phase gradient of a spinel structure of CoO2 and a layered structure of LiCoO2 was formed. Meanwhile, in the case of Comparative Example 1 in which no cobalt oxide was used, it can be seen that a coating layer having a layered structure of LiCoO2 was formed on the surface of the positive electrode active material due to the low melting point and high reactivity of Co(OH)2.
[0103] On the other hand, the average particle size (D 50 In the case of Comparative Examples 3 and 4, which do not use cobalt oxide having a particle size of 50 nm to 1000 nm, a proper coating portion is not formed, which may affect the performance of the battery due to the difference in reactivity caused by the particle size of the cobalt oxide.
[0104] Experimental example 2: Confirmation of SEM image of positive electrode active material The lithium transition metal composite oxide in the form of a single particle (composition: LiNi 0.86 Co 0.05 Mn 0.09 O2; average particle size (D 50 :4 μm) (LG Chem) was photographed using a SEM (Scanning Electron Microscope), and the SEM image is shown in FIG.
[0105] The positive electrode active materials prepared in Examples 1 and 2 and Comparative Examples 1 and 2 were photographed using an SEM. The SEM image of the positive electrode active material of Example 1 is shown in FIG. 5, the SEM image of the positive electrode active material of Example 2 is shown in FIG. 6, the SEM image of the positive electrode active material of Comparative Example 1 is shown in FIG. 7, and the SEM image of the positive electrode active material of Comparative Example 2 is shown in FIG. 8.
[0106] 4 to 8, it can be seen that in the positive electrode active material according to the present invention, the coating portion exists locally on the surface of the positive electrode active material in the form of dots, whereas in the positive electrode active materials of Comparative Examples 1 and 2, this is not the case.
[0107] Experimental Example 3: Evaluation of battery characteristics The positive electrode active materials prepared in Examples 1 and 2 and Comparative Examples 1 and 2, carbon black conductive material, and polyvinylidene fluoride (PVDF) binder were mixed in a ratio of 96:2:2 in N-methylpyrrolidone (NMP) solvent to prepare positive electrode slurry. The positive electrode slurry was applied to one side of an aluminum current collector, dried at 150° C., and rolled to prepare a positive electrode.
[0108] A lithium metal electrode was used as the negative electrode, and a porous polyethylene separator was interposed between the positive and negative electrodes to prepare an electrode assembly, which was then placed inside a battery case and an electrolyte was injected into the case to prepare a half-cell. The electrolyte was prepared by dissolving 1.0M LiPF6 in an organic solvent in which ethylene carbonate (EC): ethyl methyl carbonate (EMC): diethyl carbonate (DEC) were mixed in a volume ratio of 3:4:3.
[0109] Each half-cell thus prepared was charged at 0.1 C in CC-CV mode at 25° C. up to 4.3 V, and discharged at a constant current of 0.1 C down to 3.0 V, while measuring the initial charge capacity and initial discharge capacity, and calculating the direct current internal resistance (DCIR), which are shown in Table 1 below. For reference, the DCIR value is calculated by dividing the difference between the voltage at 60 seconds and the initial voltage while discharging at a constant current of 0.1 C by the applied current.
[0110] [Table 1] [Table 1]
[0111] In addition, the half cell prepared as described above was stored at 60°C for 12 weeks, and the volume change of the battery was measured every one or two weeks, and the results are shown in Table 2. If the reactivity increases during high-temperature storage, the amount of gas generated increases, and the volume change of the battery is large. Therefore, if the volume change of the battery is large, it can be evaluated that the high-temperature storage characteristics are poor.
[0112] [Table 2] [Table 2]
[0113] As shown in Tables 1 and 2, it can be confirmed that the batteries including the positive electrode active materials of Examples 1 and 2 not only have low initial resistance but also have a small volume change rate during high temperature storage.
[0114] On the other hand, it can be seen that the batteries including the positive electrode active materials of Comparative Examples 1 and 2, in which the coating layer including cobalt is present in a layered structure, have problems such as high initial resistance, increased side reactions during high-temperature storage due to easy release of lithium, and large amounts of gas generation. It can also be seen that the batteries including the positive electrode active materials of Comparative Examples 3 and 4, in which an appropriate coating portion is not formed, have problems such as high initial resistance and / or large amounts of gas generation.
[0115] As a result, the positive electrode active material of the present invention includes a coating portion having a phase gradient on the single particle lithium composite transition metal oxide, specifically, a coating portion having a phase gradient from a spinel structure to a layer structure from the surface to the center of the positive electrode active material, and can improve the initial resistance characteristics and storage characteristics of a lithium secondary battery. In addition, according to the method for producing the positive electrode active material of the present invention, the average particle diameter (D 50It can be seen that the positive electrode active material according to the present invention can be effectively manufactured by using cobalt oxide having a thickness of 50 nm to 1000 nm as a coating material.
Claims
1. A lithium composite transition metal oxide in the form of a single particle; and a coating portion including cobalt formed on the lithium composite transition metal oxide in the form of a single particle, The coating portion including cobalt has a phase gradient from a spinel structure to a layered structure from a surface to a center of the positive electrode active material.
2. The positive electrode active material according to claim 1 , wherein the lithium transition metal oxide in the form of a single particle contains 60 mol % or more of nickel relative to the total number of moles of metals other than lithium.
3. The positive electrode active material according to claim 1 , wherein the lithium transition metal composite oxide in the form of a single particle has a composition represented by the following Chemical Formula 1: [Chemical formula 1] Li x [Ni a Co b Mn c M1 d ]O 2-y A y In the above Chemical Formula 1, M1 is one or more selected from Y, Zr, Al, B, Ti, W, Nb, Sr, Mo and Mg; A is one or more selected from F, Cl, Br, I and S; 0.9≦x≦1.2, 0.6≦a<1, 0≦b≦0.4, 0≦c≦0.4, 0≦d≦0.2, a+b+c+d=1, and 0≦y≦0.
2.
4. The positive electrode active material according to claim 1 , wherein the coating portion containing cobalt is present locally on a surface of the positive electrode active material.
5. The coating portion containing cobalt is formed by sequentially distributing the coating portion from the surface of the positive electrode active material toward the center thereof. 3 O 4 Spinel structure of Li 0.5 CoO 2 Spinel structure of LiCoO 2 2. The positive electrode active material according to claim 1, having a phase gradient of a layered structure of
6. The positive electrode active material of claim 1 , wherein the cobalt-containing coating further comprises aluminum.
7. Single particle form lithium composite transition metal oxide and average particle size (D 50 preparing a mixture containing cobalt oxide having a thickness of 50 nm to 1000 nm; and heat-treating the mixture.
8. The mixture contains the cobalt oxide in an amount such that a ratio (B / A) of the number of moles (B) of cobalt contained in the cobalt oxide to the total number of moles (A) of metals other than lithium contained in the lithium composite transition metal oxide is 0.1 to 5. The method for producing a positive electrode active material according to claim 7.
9. The method of claim 7 , wherein the mixture further comprises an aluminum source material.
10. 10. The method of claim 9, wherein the mixture contains the aluminum source material in an amount of 0.01 to 0.1 parts by weight based on 100 parts by weight of the lithium composite transition metal oxide.
11. The method for producing a positive electrode active material according to claim 7 , wherein the heat treatment is carried out in an oxygen atmosphere.
12. The method for producing a positive electrode active material according to claim 7, wherein the heat treatment is carried out at a temperature of 600°C to 800°C.
13. The method for producing a positive electrode active material according to claim 7, wherein the heat treatment is carried out for 1 hour to 8 hours.
14. A positive electrode comprising the positive electrode active material according to any one of claims 1 to 6.
15. The positive electrode according to claim 14 ; A negative electrode; a separator interposed between the positive electrode and the negative electrode; and an electrolyte.
Citation Information
Patent Citations
Composite cathode active material, method of preparing the same, and cathode and lithium battery including the composite cathode active material
JP2019046795A
Composite positive electrode active material, positive electrode containing the same, lithium battery and manufacturing method thereof
JP2020068210A
Composite cathode active material, cathode and lithium battery comprising the same, and preparation method thereof
US20150171423A1
Cathode active material, method for manufacturing same, and lithium secondary battery comprising cathode containing same
WO2021132761A1